Epidemiological description, case-fatality rate, and trends of Hantavirus Pulmonary Syndrome: 9 years of surveillance in Argentina - Alonso, Daniel Oscar (2019)
Hantavirus pulmonary syndrome (HPS) is an endemic disease in Argentina, one of the most affected countries in the Americas. Andes virus (ANDV) is the main Orthohantavirus species causing HPS in Argentina. In this study, the geographical distribution, clinical presentation, and epidemiological features of HPS from all endemic regions of Argentina were analyzed. We focused on the clinical and epidemiological data from 533 HPS cases confirmed during the period 2009 to 2017 by the National Reference Laboratory for Hantavirus. A case-fatality rate of 21.4% was registered, and most of the cases presented a severe clinical picture requiring intensive care treatment (84%). Since HPS first detection in 1995 the case-fatality rate showed a general trend towards a decrease. After more than 22 years of experience in HPS diagnosis and surveillance, we discuss some possible factors implicated in this tendency. This clinical and epidemiological analysis gives a global perspective, being useful to detect trends and patterns, to update preventive actions at a national level, and evaluate their impact on public health.